Impact of Technology on Human Resources in Marine Logistics - Hasdinar Umar (Collaborate Engineering Daily Book Series, 2024)
Technology has significantly changed the landscape of the ocean logistics industry, affecting the roles, responsibilities, and skill needs of human resources. This research aims to explore the impact of technologies such as automation, digitalization, and information systems on human resources in ocean logistics. Through a qualitative and quantitative approach that includes a literature review, online surveys, and in-depth interviews, key findings reveal a shift in worker roles towards automation system oversight, data analysis, and strategic decision-making. New skills such as programming, data analytics, and understanding automation systems are becoming crucial. However, the industry faces challenges in recruiting a workforce with the required skills and resistance from workers to change. Strategies such as extensive training programs, collaboration with educational institutions, and effective change management help integrate technology with human resources. Technology adoption also drives changes in organizational structures and work cultures that are more collaborative and data-oriented. This research provides important insights for companies and policymakers in developing strategies to prepare a competent marine logistics workforce for digital transformation.